2020
DOI: 10.3390/antibiotics9120857
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Properties of Composite Polyethylene Materials Reinforced with Neem and Turmeric

Abstract: With the increased scientific interest in green technologies, many researches have been focused on the production of polymeric composites containing naturally occurring reinforcing particles. Apart from increasing mechanical properties, these additions can have a wide range of interesting effects, such as increasing the resistance to bacterial and fungal colonization. In this work, different amounts of two different natural products, namely neem and turmeric, were added to polyethylene to act as a natural anti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The flexural strength and modulus increased by 56.5% and 195.6%, where in the work of Sergi et al these values changed by 97% and 263%, respectively, compared to neat PP. The higher percentage increase obtained by other authors is most likely due to the lack of the addition of turmeric, which reduces the strength properties 38 , and the higher addition of a compatibilizer (5%).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The flexural strength and modulus increased by 56.5% and 195.6%, where in the work of Sergi et al these values changed by 97% and 263%, respectively, compared to neat PP. The higher percentage increase obtained by other authors is most likely due to the lack of the addition of turmeric, which reduces the strength properties 38 , and the higher addition of a compatibilizer (5%).…”
Section: Resultsmentioning
confidence: 68%
“…On other strains also showed antibacterial effects, but in a very high dose. In addition to studying the antibacterial properties of turmeric, Sunthar et al also studied its effect on mechanical properties 38 . Composites based on polyethylene with the addition of turmeric were produced.…”
Section: Introductionmentioning
confidence: 99%
“…In the last couple of years, several groups have shown that food preservation films that are made from polyethylene or sustainable materials such as seaweed can be manufactured to incorporate neem leaf extracts, neem oil, and other plant-based products (e.g., turmeric and curcumin) ( Ahmed et al, 2022 ). The resulting composite films are shelf-stable, block ultraviolet light, and have increased antifungal and antibacterial activities against C. albicans and a wide range of Gram-negative and Gram-positive organisms, including E. coli , S. aureus , Pseudomonas aeruginosa , and Bacillus subtilis ( Sunthar et al, 2020 ; Uthaya Kumar et al, 2020 ; Oyekanmi et al, 2021 ; Subbuvel and Kavan, 2021 ). Furthermore, the ability of A. indica to prevent activity of food-spoiling fungi is evident by several recent reports that outline the following: 1) the ability of neem oil to prevent the growth of the grape product-spoiling species Aspergillus carbonarius and to inhibit the production of mycotoxin by strains of this fungus ( Rodrigues et al, 2019 ), 2) the ability of neem leaves to prevent the production of aflatoxins by Aspergillus parasiticus during long-term storage of rice, wheat, and maize ( Sultana et al, 2015 ), 3) the ability of neem seed methanol and ethanol extracts to inhibit Aspergillus flavus and A. parasiticus by 10% in the context of maize storage ( An et al, 2019 ), 4) the ability of multiple neem seed, bark, and leaf extracts to inhibit the growth of three major potato-spoiling fungi, Aspergillus niger , Fusarium oxyporium , and Pythium spp., by 72–100% ( Ezeonu et al, 2019 ), and 5) the ability of aqueous neem leaf extract to inhibit growth of A. niger and A. parasiticus , as well as to detoxify aflatoxin B1 and ochratoxin A in vivo ( Hamad et al, 2021 ).…”
Section: Antibacterial Evidencementioning
confidence: 99%
“…According to a survey from World Health Organization (WHO), 600 million cases of foodborne diseases and 420,000 deaths were recorded worldwide in the year 2015. The common bacteria that responsible for the foodborne illness are Norovirus , Listeria , Campylobacter jejuni , Salmonella , Staphylococcus aureus , Escherichia coli [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, packaging plays an important role to protect food from being affected by various kinds of contaminants and preserve the products from biological, chemical and physical changes while storage or during preparation. In many so-called “advanced countries”, the food quality is a very important factor—they used to reject it even if there was a small change in the smell or appearance [ 1 ].…”
Section: Introductionmentioning
confidence: 99%